First Isolation and Characterization of Streptococcus agalactiae From a Stranded Wild Common Dolphin (Delphinus delphis) - Morick, Danny; Davidovich, Nadav; Zemah-Shamir, Ziv; Bigal, Eyal; Rokney, Assaf; Ron, Merav; Blum, Shlomo E.; Fleker, Marcelo; Soto, Esteban; Heckman, Taylor I.; Lau, Stanley C. K.; Wosnick, Natascha; et al. (Frontiers in Marine Science, 2022)
Streptococcosis is an infectious bacterial disease of both homeotherms and poikilotherms. Among the Streptococcus species that infect marine animals, Streptococcus agalactiae has the broadest host spectrum, including different aquatic organisms in freshwater and marine environments. The common dolphin (Delphinus delphis) is categorized as Endangered in the Mediterranean Sea. There are few reports of a streptococcal infection of D. delphis, caused by Streptococcus phocae and Streptococcus iniae. Here we report the isolation and identification of S. agalactiae in a stranded, wild male common dolphin that was found dead in September 2020 on the seashore next to the city of Bat-Yam, Israel. The carcass was fresh with a moderate nutritional status and with no apparent fishing gear or other anthropogenic-related signs. A post-mortem examination did not reveal an apparent cause of death, but further laboratory analysis demonstrated a S. agalactiae bacterial presence in urine, lungs and pericardial fluid that was characterized as type Ia-ST7 by whole genome sequencing. Interestingly, this isolate was found to be almost identical to another isolate recently recovered from a wild sandbar shark (Carcharhinus plumbeus) in the same area in Israel, the eastern Mediterranean Sea.